Multi-element analysis of archaeological limestone artifacts: A data-level matrix correction approach - Muskara, Uftade; Bakirdere, Sezgin; Ataman, O. Yavuz (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2026)
Elemental analysis of carbonate-rich heritage materials is often subject to strong matrix effects caused by high calcium content, which can lead to systematic underestimation of some major and trace elements, including rare earth elements (REEs), by ICP-OES and ICP-MS. This study develops a practical analytical strategy tailored to archaeological limestone artifacts, combining microwave-assisted digestion with a data-level, element-specific matrix correction based on certified reference materials (CRMs). Concentrations obtained by external calibration were empirically adjusted using correction factors derived from the ratio of standard addition to external calibration results for the CRMs NIST 1d and NCS DC 73306. This approach brought all determined element concentrations into statistical agreement with the certified values. The workflow was applied to 69 limestone figurines from the Emecik Apollo Sanctuary (T & uuml;rkiye) that were previously attributed to Cypriot sources. After matrix correction, multivariate statistical analysis of the major, trace, and REE data identified three distinct geochemical clusters, consistent with the exploitation of at least three Cypriot limestone formations. The method is minimally destructive, time-and cost-efficient, and suitable for large archaeological assemblages, providing more accurate compositional data that support reliable provenance interpretations and establish a solid geochemical basis for reconstructing raw material procurement strategies for limestone votive figurines in the ancient Eastern Mediterranean. (c) 2026 Elsevier Masson SAS. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Matrix correction; ICP-OES; ICP-MS; Provenance analysis; Rare earth elements (REEs); Emecik figurines; RARE-EARTH-ELEMENTS; ATOMIC-EMISSION-SPECTROMETRY; GEOLOGICAL SAMPLES; GEOCHEMICAL CHARACTERIZATION; PROVENANCE; TRACE; MARBLES; REE; SEDIMENTS; Archaeology; Art; Chemistry; Geology; Materials Science; Spectroscopy